Developing Students’ Creative Thinking Skills Through Art Literacy Education in Secondary Schools - Bobomurodova Sojida Ablakulovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article discusses the role of art literacy education in developing creative thinking skills among secondary school students. It explores how the integration of visual analysis, project-based learning, and interactive teaching methods contributes to students’ intellectual, emotional, and artistic growth. The paper highlights the connection between creativity and visual perception, emphasizing the importance of encouraging independent artistic decision-making and aesthetic awareness in 8th–9th grade learners.